Getting Started with Python for the Internet of Things : Leverage the full potential of Python to prototype and build IoT projects using the Raspberry Pi /: Leverage the full potential of Python to prototype and build IoT projects using the Raspberry Pi. (2019) - Cox, Tim; Dr, Fernandes, Steven Lawrence; Yamanoor, Sai; Yamanoor, Srihari; Vaish, Prof. Diwakar
No abstract available